NADPH Oxidases Play a Role in Pathogenicity via the Regulation of F-Actin Organization in Colletotrichum gloeosporioides - Liu, Na; Wang, Wenfeng; He, Chaozu; Luo, Hongli; An, Bang; Wang, Qiannan (Frontiers in Cellular and Infection Microbiology, 2022)
Multiunit-flavoenzyme NADPH oxidases (NOXs) play multiple roles in living cells via regulating signaling pathways. In several phytopathogenic fungi, NOXs are required for the polarized growth of hyphal tips and pathogenicity to host plants, but the possible mechanisms are still elusive. In our previous study, CgNOXA, CgNOXB, and CgNOXR were identified as components of the NOX complex in Colletotrichum gloeosporioides. The growth and the inoculation assays revealed that CgNOXA/B and CgNOXR regulate vegetative growth and are required for the full pathogenicity of C. gloeosporioides to Hevea leaves. We further demonstrated that the vital roles of CgNOXB and CgNOXR in appressorium formation and the development of invasion hyphae account for their functions in pathogenicity. Moreover, CgNOXB and CgNOXR regulate the production and distribution of ROS in hyphal tips and appressoria, control the specialized remodeling of F-actin in hyphal tips and appressoria, and are involved in fungal cell wall biosynthesis. Taken together, our findings highlight the role of NOXs in fungal pathogenicity through the organization of the actin cytoskeleton.